The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1136/archdischild-2021-322634
|View full text |Cite
|
Sign up to set email alerts
|

Global incidence proportion of intraventricular haemorrhage of prematurity: a meta-analysis of studies published 2010–2020

Abstract: ObjectiveTo investigate differences and calculate pooled incidence of any intraventricular haemorrhage (IVH), severe IVH (Grade III/IV, sIVH) and ventriculoperitoneal shunt (VPS) placement in preterm infants across geographical, health and economic regions stratified by gestational age (GA).DesignMEDLINE, Embase, CINAHL and Web of Science were searched between 2010 and 2020. Studies reporting rates of preterm infants with any IVH, sIVH and VPS by GA subgroup were included. Meta-regression was performed to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…While the percentage of infants with Severe Intraventricular Hemorrhage (sIVH, grade III and IV IVH) has shown a decreasing trend over time ( 57 ), a recent review showed a worldwide incidence of 6%–10% among infants born at less than 28 weeks gestational age ( 58 ). Incidence and severity of intraventricular hemorrhage are known to be higher in preterm males across birth weight categories (RR: 1.271, 95% CI: 1.207–1.338, p < 0.001) ( 35 , 36 ).…”
Section: Part I Sex Differences In Neonatal Outcomesmentioning
confidence: 99%
“…While the percentage of infants with Severe Intraventricular Hemorrhage (sIVH, grade III and IV IVH) has shown a decreasing trend over time ( 57 ), a recent review showed a worldwide incidence of 6%–10% among infants born at less than 28 weeks gestational age ( 58 ). Incidence and severity of intraventricular hemorrhage are known to be higher in preterm males across birth weight categories (RR: 1.271, 95% CI: 1.207–1.338, p < 0.001) ( 35 , 36 ).…”
Section: Part I Sex Differences In Neonatal Outcomesmentioning
confidence: 99%
“…PV-IVH occurrence, particularly severe PV-IVH, is inversely related to gestational age (GA) [ 5 7 ]. The reasons include poor coagulation, fragile microvasculature in the germinal matrix, lack of autoregulatory mechanisms in the cerebral blood flow, and increased complications and treatments associated with the small size of preterm infants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…PV-IVH occurrence, particularly severe PV-IVH, is inversely related to gestational age (GA) [5][6][7]. The reasons include poor coagulation, fragile microvasculature in the germinal matrix, lack of autoregulatory mechanisms in cerebral blood ow, and increased complications and treatments associated with the small size of preterm infants [8].…”
Section: Introductionmentioning
confidence: 99%